Psychological Distress, Pain and Insurance Claims Negatively Affect Long-Term Health-Related Quality of Life After Road Traffic Injuries - Kevin K. C. Hung; Annette Kifley; Katherine Brown; Jagnoor Jagnoor; Ashley Craig; Belinda Gabbe; Sarah Derrett; Alex Collie; Michael Dinh; Bamini Gopinath; Ian D. Cameron; on behalf of the FISH Investigators (Medical Journals Sweden, 2022)
Objective: A prospective cohort study to investigate how injury and early post-injury psychosocial factors influence health outcomes 12 months after road traffic injury. Methods: Residents of New South Wales, Australia, with road traffic injury in the period 2013-16 were recruited. Explanatory factors were evaluated for outcomes over 12 months using 12-Item Short Form Survey (SF-12) Physical and Mental Component Scores (PCS and MCS). Path models and mediation analysis were used to examine the effect of injury severity and explanatory factors. Results: SF-12 PCS and MCS outcomes were poorer among participants with baseline psychological distress, for all injury severities (β coefficients -3.3 to -9.3, p < 0.0001). Baseline pain and psychological distress, and baseline PCS and MCS were each involved in indirect effects of injury severity on 12-month PCS and MCS. Injury severity, baseline PCS and MCS, and baseline psychological distress were also associated with the likelihood of a compulsory third-party insurance claim, and claiming was negatively associated with 12-month PCS and MCS outcomes (beta coefficients -0.22 and -0.14, respectively, for both, p < 0.01). Conclusion: Baseline factors, including pain, psychological distress and lodging a compulsory third-party insurance claim, negatively impact long-term physical and mental health status following road traffic injury, emphasizing the importance of early screening and intervention. Trial registration: Australia New Zealand Clinical trial registry identification number: AC- TRN12613000889752. LAY ABSTRACT Road traffic injury (RTI) can lead to adverse long-term physical and mental health outcomes. This study followed participants with RTI for 12 months to assess the effects of acute post-injury psychological distress and physical and mental health outcomes. For physical health outcomes, greater severity of injury leads directly to a more restricted physical state; pain and psychological distress soon after injury also contribute to negative physical outcomes for participants experiencing more severe injuries. For mental health outcomes, injury severity has no direct effect on worsening mental state; mental state and psychological distress soon after injury leads to worsening outcomes for participants experiencing more severe injury. Individuals with higher psychological distress or pain were more likely to lodge a motor vehicle insurance claim. These people had subsequently poorer 12-month physical and mental health outcomes. It is essential to understand how early screening and interventions for psychological distress and pain can affect recovery.